Efeito da inflamação articular sobre o músculo esquelético: avaliação morfológica e molecular - Ramirez, Liliana Carolina Ramirez (2011)
The joint inflammation is a frequent cause of activity limitation in daily life of the population. Usually, this condition also affects the muscles that are functionally related to the inflamed joint. The possible relationship between joint inflammation and the expression of genes related to muscle atrophy, differentiation and growth and muscle mass control in muscles functionally related to the inflamed joint, has not been studied. The aim of this thesis was to evaluate the effect of the tibiotarsical joint inflammation, induced by carrageenan, on the expression of genes related to muscle atrophy (atrogin-1 and MuRF-1), growth and differentiation (MyoD), muscle mass regulation (myostatin), and proinflammatory factors (p38MAPK, NFkB and TNF-alpha); and the expression of TNF-alpha protein in the tibialis anterior (TA) and soleus rat muscle. Changes in the muscle fiber cross-sectional area (CSA) were also evaluated. Wistar rats were randomly divided into four periods (2 days, 7 days and 15 days) and were assigned into four groups within each experimental period: Control, Sham, Inflammation and Immobilization. Real-time polymerase chain reaction, Western blot, immunofluorescence and muscle fiber CSA analyses were performed. The joint inflammation altered the mRNA levels of genes related to muscle atrophy, growth and differentiation, muscle mass regulation and proinflammatory factors in TA and soleus rat muscle after 2, 7, and 15 day. The joint inflammation increased the TNF-alpha protein expression only in the TA muscle at 7 days. The muscle fiber CSA was reduced in the TA at 7 days and, in the soleus muscle at 7 and 15 days. In both muscles TA and soleus, acute joint inflammation was able to stimulate the molecular pathway related to muscle atrophy with no reduction in AST fibers. Conversely, the chronic joint inflammation led to a differential response according to the muscle studied. In the TA muscle, the muscle fiber CSA reduction was related to the proteolytic pathway, while in the soleus, the muscle atrophy occurred without overexpression of genes related to the classical proteolysis pathway. These results suggest that, in soleus muscle, the atrophy could be mediated by other pathway than the ubiquitin-proteasome; suggesting the importance of the decreased protein synthesis in the reduction of protein content in the skeletal muscle. In addition, joint effusion also induced changes in gene expression, although without changes in the muscle fiber CSA. The results of this thesis have clinical relevance and indicate the importance of therapeutic interventions with the attempt to reduce the deleterious effects on muscles related to an inflamed joint.